New evidence on redlining by federal housing programs in the 1930s - Price Van Meter Fishback; Jonathan Rose; Kenneth A. Snowden; Thomas Storrs (Federal Reserve Bank of Chicago, 2022)
We show that the Federal Housing Administration (FHA), from its inception in the 1930s, did not insure mortgages in low income urban neighborhoods where the vast majority of urban Black Americans lived. The agency evaluated neighborhoods using block-level information collected by New Deal relief programs and the Census in many cities. The FHA's exclusionary pattern predates the advent of the infamous maps later made by the Home Owners' Loan Corporation (HOLC) and shows little change after the drafting of those maps. In contrast, the HOLC itself broadly loaned to such neighborhoods and to Black homeowners. We conclude that the HOLC's redlining maps had little effect on the geographic distribution of either program's mortgage market activity, and that the FHA crafted and implemented its own redlining methodology prior to the HOLC.
Keywords: N22; G21; R38; J15; 330; Redlining; mortgage history